Floristic composition and ecological-biological characteristics of avalanche path vegetation of Central Altai - Kosachev, Petr A.; Bykov, Nikolay I.; Grokhlina, Tatiana I.; Ovcharova, Natalia V. (Acta Biologica Sibirica, 2025)
The article analyzes the floristic composition, ecological groups in relation to soil moisture and substrate, and life forms in the phytocenoses of avalanche paths in Central Altai. It was found that the species composition of the plant communities of the avalanche paths of Central Altai differs significantly. The floristic similarity of the communities, estimated by the index of biotal dispersion (IBD), is weak in all parts of avalanche paths and reaches the highest value (14.2 %) for undisturbed forest communities (Z), and the lowest (9.3%) – in sites X, the central parts of avalanche paths. Data on the higher biodiversity of the central parts of avalanche paths (X) compared to the surrounding forest communities have been confirmed. It was found that family Gentianaceae and genus Gentiana indicate the central parts of avalanche paths, where avalanches occur most frequently. Shrub species of genera Salix and Betula and Lonicera altaica are characteristic of the avalanche path vegetation, have a high abundance, indicate frequent avalanching and can be indicators of avalanche ecotopes. At the same time, species of genus Betula (B. humilis, B. rotundifolia) and Lonicera altaica have high projective cover at level of the B track, while Salix glauca has high projective cover at level of the C track. Using the EcoScaleWin program, geobotanical descriptions on the ecological scales of D.N. Tsyganov were processed to assess the ecological conditions of ecotopes in avalanche paths of Central Altai. In turn, we used the obtained values of ecological scales to identify the dependencies between factors and their influence on the ecotopes using the principal component analysis (PCA). According to the analysis, in the central areas in avalanche paths located on the northwestern slopes, vegetation is influenced to a greater extent by 4 factors: high soil moisture, their nitrogen richness, salt richness, and lower soil acidity. However, in sites X (the central trough) there are more ecotopes, the soils of which are rich in nitrogen and salts, in sites Y (intermediate sections) soil moisture plays an important role. Ecotopes with high shading are typical for forest communities (sites Z). The sites of the avalanche paths studied are located in the forest belt, which is emphasized by the predominance of mesophytes and a high percentage of short-rhizome and long-rhizome herbs in the avalanche paths of Central Altai. Besides, in the central areas of the paths in avalanching sites, there is a high proportion of plants living on waterlogged soils, including cold and moist soils (hygrophytes, hygropsychrophytes, mesohygrophytes, psychrophytes, and mesopsychrophytes), i.e. these ecological groups are indicators of avalanche paths and point out frequent avalanches. On the eastern and southeastern (less often northwestern but then on rocky substrates) slopes in sites X and Y, species of dry and rocky habitats appear in the avalanche paths – xerophytes and petrophytes, many of which are tap-rooted herbs. In the spectrum of life forms of the avalanche paths of Central Altai, in addition to the predominant short-rhizome, long-rhizome and tap-rooted herbs, there is a large proportion of shrubs and brush-rooted herbs in the central parts, indicating frequent avalanches. In open areas, shrubs are abundant in herbaceous-shrubby communities, they are dominant and edificators. In general, short-rhizome, tap-rooted, and brush-rooted herbs (as well as brush-rooted tuber-forming and bulbous), which dominate in shrub-herbaceous cenoses of the avalanche paths, are confined to habitats with poor soil aeration in the X and Y sites; in forest communities (site Z), long-rhizome and loose-bush (also creeping herbs) are characteristic of sufficiently moist and loose soils.